Validation of Universal Scale in Oral Surgery (USOS) for Patient’s Psycho-emotional Status Rating - Astramskaite, Inesa (J Oral Maxillofac Res, 2017)
OBJECTIVES: There aren’t any objective methods that may help in standard evaluation of oral surgery patient’s psycho-emotional status. Without any standardized evaluation, two main problems appear: heterogeneity between studies and ineffective patient’s evaluation. Therefore, Universal Scale in Oral Surgery (USOS) for patient’s psycho-emotional status rating has previously been proposed by authors. The aim of present study is to assess the clinical effectivity and validate the Universal Scale in Oral Surgery in case of outpatient tooth extraction for adult healthy patients. MATERIAL AND METHODS: Clinical trial to validate the USOS for patient’s psycho-emotional status rating was performed. In total 90 patients, that came for outpatient dental extraction to Lithuanian University of Health Sciences Oral and Maxillofacial Surgery Department ambulatory, were enrolled in clinical trial. Patients filled self-reported questionnaires before the procedure. Operating surgeon rated USOS for patient’s psycho-emotional status rating doctor’s part questionnaire after the procedure. 4 - 6 weeks later all patients were asked to fill USOS for patient’s psycho-emotional status rating questionnaire retrospectively. RESULTS: According to the statistical analysis, the final composition of USOS for patient’s psycho-emotional status rating that would fit to reliability coefficient should be composed from 6 patient part questions and 3 general doctor part questions. CONCLUSIONS: Universal Scale in Oral Surgery for patient’s psycho-emotional status rating is a novel, doctor and patient rated scale which is suitable for clinical and scientific usage.